1996
DOI: 10.1161/01.str.27.6.1023
|View full text |Cite
|
Sign up to set email alerts
|

Weekend and Holiday Increase in the Onset of Ischemic Stroke in Young Women

Abstract: We found that young adults and women are frequently stricken by brain infarction during weekends and holidays and that the circadian distribution of the onset of brain infarction among young adults is different from that of middle-aged people. These observations suggest that there may be stroke-triggering activities that are associated with lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 25 publications
6
42
1
4
Order By: Relevance
“…In the gender, and other studies found the lowest incidence for women in August, and for men in June (15). Other studies showed the highest incidence in January for all stroke types (15), and in Septembar (16). The highest incidence of ICH is found in February but the lowest in August (5), and we found that May is month with the most ICH, and July and October with the least ICH occurences.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In the gender, and other studies found the lowest incidence for women in August, and for men in June (15). Other studies showed the highest incidence in January for all stroke types (15), and in Septembar (16). The highest incidence of ICH is found in February but the lowest in August (5), and we found that May is month with the most ICH, and July and October with the least ICH occurences.…”
Section: Discussionsupporting
confidence: 65%
“…Other studies showed the highest incidence in January for all stroke types (15), and in Septembar (16), while the highest incidence of ICH is in February but the lowest in August. (5) The incidence was higher in the summer season for IS (16), other studies showed the highest incidence of IS during the winter (5), or in autumn (17).…”
Section: Introductionmentioning
confidence: 87%
“…Other Finnish studies have also suggested that acute intoxication might be associated with ischemic stroke in women, especially young women. 106,107 An increased risk of subarachnoid hemorrhage was observed among women who drank more than 1.2 drinks per day in the Nurses Health Study, 65 and trends toward increased hemorrhagic stroke have been observed in other cohort studies of women. 71,108 An evaluation of U.S. mortality data for 1987 suggested that women experienced greater alcohol-related cardiovascular mortality than men, largely due to cerebrovascular disease.…”
Section: Medical Risks Of Drinking For Women Compared With Menmentioning
confidence: 90%
“…This could lead to an enhancement of the harmful effects of alcohol, including alcoholic liver disease and upper gastrointestinal cancer. The impact of alcohol consumption on weekdays or at weekends has only been addressed in few previous studies (Haapaniemi et al, 1996;Bråthen et al, 2000;Trevisan et al, 2004). The studies indicate that the Cardiovascular death Figure 1 On a logarithmic scale the RR of death from all causes and cardiovascular disease is shown in relation to intake of alcohol in drinks per week.…”
Section: Previous Studiesmentioning
confidence: 99%
“…One study among men and women aged 16-60 years find that recent drinking of alcohol were associated with onset of brain infarction during weekends and holidays (Haapaniemi et al, 1996). One study investigated the impact on risk of myocardial infraction (Trevisan et al, 2004).…”
Section: Previous Studiesmentioning
confidence: 99%